Pengembangan Modul Hidrolisis Garam Berbasis Guided Discovery Learning Untuk Peserta Didik Kelas XI SMA atau MA - Puti Ika Artika; Bayharti Bayharti (Universitas Negeri Padang, 2021)
This research aims to develop and reveal the validity category of salt hydrolysis module based on guided discovery learning. The type of this research is a Research and Development (R and D). This research used Plomp model which consists of preliminary research, prototype, and assessment phases stage. This research is limited to the prototype stage that is prototype II. This module was validated by three lecturers from Chemistry Department FMIPA UNP and two chemistry teachers from SMAN 1 2X11 Kayutanam. The results of the validity test showed that the eligibility of module content has a category valid (V=0.87), linguistic component has a validity category moderate (V=0.8), serving component has a category valid (V=0.89), and graphic component has a category valid (V=0.85). It can be concluded that the module developed has a category valid with average V of 0.85.